1982
DOI: 10.1128/iai.35.2.685-696.1982
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of mice by intracutaneous inoculation with viable virulent Cryptococcus neoformans: immunological and histopathological parameters

Abstract: Immune responses, including protection and delayed hypersensitivity, were evaluated in experimental murine cryptococcosis. Mice were immunized by the intracutaneous inoculation of viable virulent Cryptococcus neoformans yeasts. Response to the cutaneous infection was evaluated histologically and by cultural assays of the internal organs, as well as by intravenous challenge with the same strain. Protection was assessed by survival, histopathology, and quantitative organ culture. The intracutaneous inoculation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…There has been very little evaluation of how different routes of cryptococcal inoculation cause infection, and strain and host factors are likely to significantly affect the pattern of dissemination. One study suggests that intracutaneous inoculation is less likely to result in systemic infection, 22 but more work is needed to clarify this. The authors hypothesise that both bone lesions occurred secondary to haematogenous spread from the respiratory tract, rather than a penetrating wound leading to disseminated infection.…”
Section: Discussionmentioning
confidence: 99%
“…There has been very little evaluation of how different routes of cryptococcal inoculation cause infection, and strain and host factors are likely to significantly affect the pattern of dissemination. One study suggests that intracutaneous inoculation is less likely to result in systemic infection, 22 but more work is needed to clarify this. The authors hypothesise that both bone lesions occurred secondary to haematogenous spread from the respiratory tract, rather than a penetrating wound leading to disseminated infection.…”
Section: Discussionmentioning
confidence: 99%
“…Inbred young adult mice infected systemically with a lethal inoculum of C. neoformans exhibit a profound meningoencephalitis. Typically, brain yeast burdens are 暇10 8 , and histological examination of brain tissue shows severe necrosis and edema (16,39,43). Moribund C. neoformans-infected mice have marked loss of appetite and weight and exhibit hydrocephaly.…”
Section: Greater Susceptibility Of Aged Mice Than Of Young Adult Micementioning
confidence: 99%
“…The histopathology of murine cryptococcosis is well studied with conventional methods [5,10]. Immunohistological differentiation of leucocyte subsets has been performed for the lung [11,12,13] after intratracheal infection with C. neoformans and in human pulmonary cryptococcosis [14], but not for cryptococcal meningoencephalitis after intravenous infection.…”
Section: Introductionmentioning
confidence: 99%
“…The infiltration of CD4+ and CD8+ cells into the liver and brain of infected mice provide additional support to these findings. Similarly, depletion experiments showed that CD8+ cells are essential for the generation of delayed-type hypersensitivity (DTH) in murine cryptococcosis [ ci was found to be associated with better protection against secondary infection with the fungus, although no histological differences in pathology of the internal organs between immunized and unimmunized mice could be demonstrated [10]. These works, with the exception of a recent publication by Hill and Aguirre [37], focused on the importance of local immunity in the lungs against dissemination of the fungus to extrapulmonary sites.…”
mentioning
confidence: 99%